Implementation of MC Kinsey's 7S Framework as a Strategy to Improve the Performance of Educational Institutions - Jubaedah, Edah; Sudirman, Iman; Djulius, Horas (IJBLE Scientific Publications Community Inc., 2025)
McKinsey's 7S framework is a tool used to analyze the internal aspects of a company's organization using 7 main elements: Strategy, Structure, System, Shared Values, Style, Staff and Skills. Institutional performance using the Nine Key Indicators Criteria, namely: Vision, Mission, Goals and Strategies; Governance, Governance and Cooperation; Students; Human Resources; Finance, Facilities, Infrastructure; Education; Research; Community Service; Tridharma Outputs and Achievements. This research was conducted through a qualitative approach with descriptive methods and using SWOT Analysis and Nvivo 12 For Windows Software so that accurate and detailed data were obtained involving ten key informants from Nurtanio University Bandung officials, resulting in a Strategy for Optimizing the Application of McKinsey's 7S Framework in Efforts to Improve the Performance of University Institutions. Unnur's functional strategies include: Human Resources Strengthening Strategy, Important Role of the Finance Department, Research and Development / Innovation Implementation Strategy, External Strengthening Strategy. With these strategies and programs, Unnur is expected to improve institutional performance.